Causation, Types and Outcome of Road Traffic-related Ocular Injury in University of Llorin, Kwara, Nigeria - Olawale Job Oladejo; Dupe Serifat Ademola-Popoola; Amase Nyamngee; Folu Owoeye (Journal of Clinical and Diagnostic Research, 2024)
Introduction: Despite transportation liberating man and making him mobile, his increasing reliance on vehicular movement has conferred great facilities on him and his activities. The most profound culprit of all modes of transport is the road, of which traffic accidents are the most disturbing consequence of its use. Road traffic-related ocular injuries often have severe consequences and form a significant part of ophthalmic emergencies. These injuries may be missed and are therefore often underreported. Aim: To determine the causation, types, and outcomes of road traffic-related ocular injuries at the University of Ilorin Teaching Hospital, Kwara, Nigeria. Materials and Methods: This was a cross-sectional study conducted on 78 eyes of consecutive patients with road traffic-related ocular injuries who presented at the Accident and Emergency unit of the University of Ilorin Teaching Hospital, Kwara, Algeria, between September 2012 and August 2013. The materials included the HOTV chart for vision assessment, which is a standardised, easy-to-use assessment method for both literate and illiterate individuals, a pen torch, direct ophthalmoscope, binocular indirect ophthalmoscope, slit lamp biomicroscope, Perkins tonometer, 2% fluorescein strip, 0.5% GuttTetracaine, and a handheld portable slit lamp ophthalmoscope. Patients’ demographics, duration of ocular injury before presentation, Visual Acuity (VA) at presentation, type of vehicle, place of injury, classification of ocular injury, treatment, and outcome on follow-up were recorded. Results: There were 78 eyes (72 patients) with road traffic-related ocular injuries. The age range of the subjects was 3-55 years with a mean of 31.10 years. Forty-four (61.1%) patients were young men between 20-39 years. Fifty-one (70.8%) patients were males, and 21 (29.2%) were females, with a male-to-female ratio of 2.4:1. Most of the victims were traders (22, 30.6%), and fifty-two eyes (72.2%) presented within 12 hours of ocular injury. Motorcycles were associated with ocular injury in 37 (51.4%) patients. The most common injuries were of closed globe type (contusion, lamellar laceration, superficial foreign body) in 70 patients (89.7%). Conclusion: Road traffic-related injuries have increased over the past eight years in Nigeria. Males are more commonly injured in Road Traffic Injury (RTI), and motorcycles were the most common cause of injury to road users. Three out of 36 people injured in a vehicle at the time of injury used seat belts, while none of the riders and passengers on motorcycles wore helmets. The importance of prevention, the use of safety devices, and the avoidance of risk behaviors on the road need to be emphasised.